2015
DOI: 10.4049/jimmunol.1303316
|View full text |Cite
|
Sign up to set email alerts
|

High Mitochondrial Respiration and Glycolytic Capacity Represent a Metabolic Phenotype of Human Tolerogenic Dendritic Cells

Abstract: Human dendritic cells (DCs) regulate the balance between immunity and tolerance through selective activation by environmental and pathogen-derived triggers. To characterize the rapid changes that occur during this process, we analyzed the underlying metabolic activity across a spectrum of functional DC activation states, from immunogenic to tolerogenic. We found that in contrast to the pronounced proinflammatory program of mature DCs, tolerogenic DCs displayed a markedly augmented catabolic pathway, related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
179
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(206 citation statements)
references
References 35 publications
25
179
1
1
Order By: Relevance
“…Metabolic studies in macrophages have revealed differential pathways regulated during differentiation into M1 and M2 phenotypes (710). Similar studies have been undertaken for T helper cell subsets (6, 11, 12), dendritic cells (13), and to a limited extent also in monocytes (5). In well-perfused inflamed tissues like the synovial membrane in rheumatoid arthritis, where nutrients are in ample supply, the massively upregulated glycolytic flux of activated monocytes and macrophages is sustained by high glucose consumption.…”
Section: Introductionmentioning
confidence: 64%
“…Metabolic studies in macrophages have revealed differential pathways regulated during differentiation into M1 and M2 phenotypes (710). Similar studies have been undertaken for T helper cell subsets (6, 11, 12), dendritic cells (13), and to a limited extent also in monocytes (5). In well-perfused inflamed tissues like the synovial membrane in rheumatoid arthritis, where nutrients are in ample supply, the massively upregulated glycolytic flux of activated monocytes and macrophages is sustained by high glucose consumption.…”
Section: Introductionmentioning
confidence: 64%
“…50 Tolerogenic DCs display enhanced glycolytic capacity and ROS production with respect to mature pro-inflammatory DCs. 51 PM significantly increases intracellular ROS in human DCs, which were inhibited by alum. Recently, D-mannose treatment increased ROS production in T cells compared with TCR stimulation alone.…”
Section: Discussionmentioning
confidence: 93%
“…This conclusion is based on metabolic analyses of tolerogenic human DCs (Malinarich et al, 2015), as well as the fact that resveratrol, a drug that promotes OXP HOS, and vitamin-D3 and dexamethasone, which promote the expression of genes related to OXP HOS, enhance DC tolerogenicity (Rachamim et al, 1995;Švajger et al, 2010;Ferreira et al, 2015). Recent work has emphasized the complexity of the role of lipid metabolism in the regulation of DC function.…”
Section: Switching To Warburg Metabolism Allows Cellular Activation Amentioning
confidence: 99%